1994
DOI: 10.1002/j.1460-2075.1994.tb06654.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a birch pollen allergen, Bet v III, representing a novel class of Ca2+ binding proteins: specific expression in mature pollen and dependence of patients' IgE binding on protein-bound Ca2+.

Abstract: A cDNA coding for a birch pollen allergen, Bet v III, with significant sequence homology to Ca2+ binding proteins was isolated from an expression cDNA library using serum IgE from a patient who was allergic to pollen. The deduced amino acid sequence of the pollen allergen contained three typical Ca2+ binding sites. Peptides mimicking the Ca2+ binding sites of Bet v III were synthesized and shown to bind 45Ca in blot overlays. The binding of patients’ IgE to the recombinant allergen depended on the native prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
100
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 41 publications
0
100
0
1
Order By: Relevance
“…Immunolocalization of some BPC1 in the pollen walls was observed after hydration and germination, suggesting that leakage of the protein from the cytosol to the wall occurred as the grains hydrated. In addition, BPC1-related proteins have been characterized as human allergens (Knox et al, 1992;Toriyama et al, 1995;Batenero et al, 1997;Engel et al, 1997;Suphioglu et al, 1997;Twardosz et al, 1997), as have the BET vIII and BET vI pollen proteins, which have 2-to 2.5-fold greater molecular masses than BPC1 (Vrtala et al, 1993;Seiberler et al, 1994). This allergenicity implies a pollen-surface location or release upon pollen hydration.…”
Section: Discussionmentioning
confidence: 99%
“…Immunolocalization of some BPC1 in the pollen walls was observed after hydration and germination, suggesting that leakage of the protein from the cytosol to the wall occurred as the grains hydrated. In addition, BPC1-related proteins have been characterized as human allergens (Knox et al, 1992;Toriyama et al, 1995;Batenero et al, 1997;Engel et al, 1997;Suphioglu et al, 1997;Twardosz et al, 1997), as have the BET vIII and BET vI pollen proteins, which have 2-to 2.5-fold greater molecular masses than BPC1 (Vrtala et al, 1993;Seiberler et al, 1994). This allergenicity implies a pollen-surface location or release upon pollen hydration.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be postulated that the above potential family of pollen proteins may have a function in this tissue that is related to its Ca*+-binding ability. The birch allergen Bet v 111, which also contains Ca'+-binding sites [32], is unlikely to belong to this family of pollen proteins because of its molecular mass (26 m a ) , the presence of four Caz+-binding sequences, and the absence of sequence similarity with Bra r I and Bra r I1 except for the EF-hand motifs [30].…”
Section: Discussionmentioning
confidence: 99%
“…In this context it was found that several calcium-binding allergens exhibited varying IgE binding capacities depending on the presence or the absence of proteinbound calcium (24,43). To test the influence of calcium on the IgE binding of recombinant carp parvalbumin, we exposed sera from six representative fish-allergic patients to nitrocellulose-blotted rCyp c 1.01 in the presence (ϩ lanes ) or the absence (Ϫ lanes ) of protein-bound calcium (Fig.…”
Section: Calcium Depletion Leads To a Reduction Of Ige Binding To Rcymentioning
confidence: 99%